Concept of Islamic Education from Muhammad Abduh's Perspective - Muhammad Sofiullah (Elementaria: Journal of Educational Research, 2023)
Muslims have figures who have greatly contributed to the fields of medicine, philosophy, education, mathematics, political astronomy and others. One of them is Muhammad Abduh, he is a Muslim intellectual figure in the modern era who carried out Islamic reforms in all scientific fields, especially in the field of Islamic education. With this, the author wants to understand the concept of Islamic education from Muhammad Abduh's perspective. This research is included in qualitative research based on literature study. The data sources in this research analyze works, books and journals related to the figure Muhammad Abduh. The results of the research explain that the main points of Muhammad Abduh's thoughts in Islamic education are: liberation of thought from taqlid, purification of Islamic religious teachings, renewal in Islamic education.